Understanding policy : an interpretive moment - French, Lesley D. (Curtin University, 2011)
This study considers the meaningfulness of policies and proposes that a trustworthy interpreting of a policy can be undertaken by assuming varied philosophical perspectives. It presumes that policies may mystify an interpreter, and, therefore, the purpose is to demonstrate that the meanings given to a policy should always be open to question.In interpreting policy, philosophical perspectives can be used as frames to disclose understandings that may not be at first available to an interpreter, particularly where a single meaning dominates or where meanings might be absent or vague. By applying varied perspectives to a policy, there is potential for meanings that are considered truthful to be displayed and many possible trustworthy understandings to be disclosed.In this study, the Tasmanian public education policy Learning Together is interpreted using frames in which philosophical ideas are used heuristically as metaphors. The first frame is language, and specifically metaphor as discussed by George Lakoff and Mark Johnson, the second engages ideas from selected works of Michel Foucault, and the third takes up ideas from the work of Hans-Georg Gadamer. Each frame enables differing understandings of the Learning Together policy to emerge, revealing how language, power and self-understanding might influence the meanings given to that policy.This approach can be understood as philosophically interpretive as it acknowledges the complexities of understanding in the first decade of the twenty-first century, where assumptions of indisputable truths or realities are under question. It can be thought of as philosophising as it fosters more reflective understanding of policy and enables greater consciousness of the diversity of meanings that may be attributed to policies.